Propositional logic proof

In summary: A > (B v ~C) 2-11 conditional introductionThis shows that * > (B v ~C). So the whole thing follows by conditional introduction from that. It's been a while since I've done this so I might have missed something.In summary, the statement (A \supset B) \wedge (B \supset C) \wedge (D \supset \neg C) \wedge (A \vee D) \models (B \vee \neg C) is proven to be true by using the logical deduction system SD. The proof involves assuming the premise (*), and then using conjunction elimination, conditional elimination, disjunction introduction, and
  • #1
gnome
1,041
1
I want to prove [itex](A \supset B) \wedge (B \supset C) \wedge (D \supset \neg C) \wedge (A \vee D) \equiv (B \vee \neg C)
[/itex]
so I have to show that [itex]\neg ( ((A \supset B) \wedge (B \supset C) \wedge (D \supset \neg C) \wedge (A \vee D)) \supset (B \vee \neg C))[/itex]
is inconsistent, and I proceed as follows:

[tex]\begin{array}{ccccccccccc}\neg ( ((A \supset B) &\wedge &(B \supset C) &\wedge &(D \supset \neg C) &\wedge &(A \vee D)) &\supset (B \vee \neg C))\\

\neg ( \neg((A \supset B) &\wedge &(B \supset C) &\wedge &(D \supset \neg C) &\wedge &(A \vee D)) &\vee &(B \vee \neg C))\\

((A \supset B) &, &(B \supset C) &, &(D \supset \neg C) &, &(A \vee D)) &, &\neg (B \vee \neg C))\\

(\neg A \vee B) &, &(\neg B \vee C) &, &(\neg D \vee \neg C) &, &(A \vee D) &, &\neg B&, &C))\\

\text{contradiction}&, &\neg B &, &\neg D&, &A &, &\neg B &, &C

\end{array}[/tex]

so I end up with a contradiction showing that the original statement is correct.

Question: is there a "better", more formal way to present this proof?
 
Last edited:
Physics news on Phys.org
  • #2
You seem to have that screwed up. for instance in case A is false but B is true, then the left side is false but the right side is true, so they are not equivalent.




Maybe instead of the last two operational symbols being "and" , then "equivalence", they should be the opposite order, "equivalence", then "and".

i.e. the following two statements might be equivalent:

I. C implies B and B implies A, and notC implies D,

II. [either B or notC], and[ either A or D].

at least I implies II. let see... no that doesn't work either. then if B is true and A is true, but D is false, one side is true and the other is false.
 
  • #3
Assuming I didn't make a mistake, it seems to me that what you're trying to prove is false (so you can't prove it). Make a truth table, the two sentences aren't "nearly" equivalent.
 
  • #4
So sorry. I meant to write:

[itex](A \supset B) \wedge (B \supset C) \wedge (D \supset \neg C) \wedge (A \vee D) \models (B \vee \neg C)
[/itex]

as the first line.
 
  • #5
what do the symbols mean? especially that one that now replaces equivalence?
 
  • #6
I believe it is read "yields" if it is the same as |-


I've seen it used in place of the logical implication symbol so I guess they are the same thing.
 
  • #7
The meanings are similar but not exactly the same.

According to what I've read so far, the first one, [itex]\models[/itex], is called the "semantic turnstile".
[tex]\begin{array}{lll} \text{if} \;&\{a_1, a_2, ..., a_n\} &\models A\\
\text{then} \; &\{a_1, a_2, ..., a_n\} &\supset A \; \text{is a tautology}\end{array}[/tex]
or we can say that A is a logical consequence of {a_1, a_2, ..., a_n}.

The other one, [itex] \vdash[/itex], I think is called the "syntactic turnstile". and
[tex]\{a_1, a_2, ..., a_n\} &\vdash A[/tex]
means that A can be proved from [itex]\{a_1, a_2, ..., a_n\}[/itex] by using a set of syntactic rules.

But frankly, I can't say that I'm clear about exactly what the difference is between those two statements, so I'd love to hear a better explanation from someone who knows. :smile: :smile:
 
Last edited:
  • #8
gnome said:
So sorry. I meant to write:

[tex](A \supset B) \wedge (B \supset C) \wedge (D \supset \neg C) \wedge (A \vee D) \models (B \vee \neg C)[/tex]

as the first line.
This is easy to prove. As far as I know, it should technically be written as:

[tex]\{(A \supset B) \wedge (B \supset C) \wedge (D \supset \neg C) \wedge (A \vee D)\} \models (B \vee \neg C)[/tex]

since it is a set of sentences which are said to entail a conclusion sentence. I'm not sure what system of deduction you're using. The only one I'm familiar with is SD. Let's replace the premise by *.
Code:
1  | *                             Assumption
   |------------------------------
2  | | A                           Assumption
   | |----------------------------
3  | | A > B                       1 conjunction elimination
4  | | B                           2-3 conditional elimination
5  | | B v ~C                      4 disjunction introduction
   |
6  | | D                           Assumption
   | |----------------------------
7  | | D > ~C                      1 conjunction elimination 
8  | | ~C                          6-7 conditional elimination
9  | | B v ~C                      8 disjunction introduction
   |
10 | A v D                         1 conjunction elimination
11 | B v ~C                        10, 2-5, 6-9 disjunction elimination
 

1. What is propositional logic proof?

Propositional logic proof is a method of using logical arguments to demonstrate the validity of a statement or argument in propositional logic. It involves breaking down a statement into simpler propositions and using logical rules and inference rules to show that the statement is true or false.

2. What is the difference between propositional logic proof and predicate logic proof?

The main difference between propositional logic proof and predicate logic proof is that propositional logic deals with simple propositions, while predicate logic deals with more complex statements that contain variables and quantifiers. Additionally, propositional logic proof uses only logical rules and symbols, while predicate logic proof also incorporates rules of inference from mathematics and set theory.

3. What are the basic logical rules used in propositional logic proof?

The basic logical rules used in propositional logic proof include the rules of logical equivalence, negation, conjunction, disjunction, implication, and biconditional. These rules allow us to manipulate propositions and create new ones based on their truth values.

4. How do you construct a propositional logic proof?

To construct a propositional logic proof, you first need to identify the premises and conclusion of the argument. Then, you can use the basic logical rules and inference rules to manipulate the premises and show that the conclusion logically follows. It is important to carefully track the truth values of each proposition and clearly state each step in the proof.

5. What are some common mistakes to avoid in propositional logic proof?

Some common mistakes to avoid in propositional logic proof include using incorrect logical rules, making invalid assumptions, and not keeping track of the truth values of each proposition. It is also important to clearly state each step in the proof and avoid vague or ambiguous language. Additionally, it is important to check the validity of the proof by considering counterexamples or using truth tables.

Similar threads

  • Set Theory, Logic, Probability, Statistics
Replies
16
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
6
Views
944
  • Calculus and Beyond Homework Help
Replies
2
Views
869
  • Set Theory, Logic, Probability, Statistics
Replies
3
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
5
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
7
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
5
Views
2K
Back
Top